STANDAR PROSEDURAL DAN KEKUATAN PEMBUKTIAN PENYADAPAN DALAM TINDAK PIDANA KORUPSI - Pakpahan, Novritsar Hasitongan; Waskito, Sarwo; Wijaya, Kurnia; Khayru, Rafadi Khan; Saputra, Rio (Gapenas Publisher, 2025)
This normative legal study examines the practice of wiretapping as evidence in proving corruption crimes in Indonesia, focusing on proof standards and privacy protection. The research aims to analyze the lawful procedural standards for wiretapping, the position and probative value of wiretapping results as electronic evidence in court, and potential legal disputes arising from its implementation. The study employs a qualitative literature review method, analyzing primary legal materials such as the Corruption Eradication Commission Law, the Electronic Information and Transaction Law, the Criminal Procedure Code, and relevant Constitutional Court decisions. The findings indicate that wiretapping's legality is based on a complex regulatory interaction, requiring strict adherence to procedural standards including a clear legal basis, authority from competent institutions, supervision mechanisms, and proportionality principles. The position of wiretapping results as evidence is recognized under electronic evidence provisions, yet its probative strength is contingent upon factors of legality, integrity, relevance, and adherence to due process. Potential legal disputes encompass challenges to authority, procedural violations, constitutional rights infringements, and technical authenticity, each carrying significant implications for the admissibility of evidence. The study concludes that while wiretapping is a potent tool against corruption, its application must rigorously balance law enforcement objectives with fundamental rights protections within Indonesia's rule of law framework.